Quality uncertainty with imperfect information acquisition - Christopher Gertz (Bielefeld University, Center for Mathematical Economics (IMW), 2013)
I analyze a monopolistic model of quality uncertainty but with the possibility of information acquisition on the consumer side. Information is costly and its amount is chosen by the consumer. The analysis of Bayesian equilibria shows the possibility of three equilibrium classes, only one of which leaves positive utility to the consumer. The classic adverse selection results of these markets are weakened in this situation. I show that cheaper information does not necessarily benefit the consumer but can instead rule out the buyer-friendly and welfare maximizing equilibria. Moreover, making quality search arbitrarily efficient does not lead to sure selling of the high quality product. A sustainable adverse selection effect, though weaker than in the classical model, remains even in the limit.
Keywords: 330